Epidemiology of Adenovirus Pneumonia and Risk Factors for Bronchiolitis Obliterans in Children During an Outbreak in Jilin, China - Yu, Xiuhua; Ma, Yucong; Gao, Yang; You, Hailong (Frontiers in Pediatrics, 2021)
Abstract Background: Jilin Province, located in northeastern China, recently experienced a human adenovirus (HAdV) epidemic. Few studies involving hospitalized pediatric patients with pneumonia caused by HAdV in our region exist. HAdV pneumonia can lead to severe long-term respiratory sequelae, such as postinfectious bronchiolitis obliterans (PIBO), which has a poor prognosis and greatly influences the quality of life of pediatric patients. However, studies on the risk factors for PIBO are limited. Objective: To describe the HAdV pneumonia prevalence and determine potential risk factors for PIBO development among hospitalized children in Jilin Province, China. Methods: The data of 187 children with HAdV pneumonia (10 months-12 years old) admitted to the First Hospital of Jilin University during an outbreak between October 2018 and January 2020 were retrospectively studied. We analyzed the epidemiological characteristics of HAdV pneumonia, focusing on severe HAdV pneumonia (66 cases). The risk factors for BO development were determined by comparing the demographic and clinical data of the BO and non-BO groups. Results: The largest number of HAdV pneumonia cases occurred in January 2019 (severe n=18, general n=21), followed by December 2018 (severe n=14, general n=11), June 2019 (general n=17), July 2019 (general, n=14), and May 2019 (general, n=13). In total, 91.98% of the children with HAdV pneumonia were less than 6 years old (172/187), and 50% of the pediatric patients with severe HAdV pneumonia were less than 2 years old (33/66). We found that 30.3% of the severe cohort developed BO (20/66), and the strongest independent risk factors for PIBO were persistent wheezing (OR 181.776, 95% CI, 3.385-9761.543) and acute respiratory failure (OR 51.288, 95% CI, 1.858-1415.441) during a severe pneumonia episode. Conclusions: The largest number of HAdV pneumonia cases, especially severe cases, occurred in winter in Northeast China, followed by summer. The majority of children admitted with HAdV pneumonia were less than 6 years old, and half of severe HAdV pneumonia patients were < 2 years old. Children who had persistent wheezing or acute respiratory failure during the acute phase of severe HAdV pneumonia were prone to the development of BO.